The Effect of Stress and Work Discipline on the Performance of Employees of PT. SDL with Organizational Citizenship Behavior (OCB) as an Intervening Variable - Antonius Rio Sandi; Setyo Riyanto (Raudhah Publisher, 2026)
This study aims to explain how the influence of stress and work discipline on employee performance with organizational citizenship behavior (OCB) as an intervening variable. This study used 109 respondents of employees of PT. SDL as a sample. Data collection using questionnaire. This study used Structural Equation Modeling (SEM) data analysis with instrument testing used the Partial Least Square (PLS) method. The result of this study that (1) Work stress has a negative and significant effect on Organizational citizenship behavior (OCB), (2) Work discipline has a positive and significant effect on Organizational citizenship behavior (OCB), (3) Work stress has a negative and significant effect on employee performance, (4) Work discipline has a positive and significant effect on employee performance, (5) Organizational citizenship behavior (OCB) has a positive and significant effect on employee performance, (6) Work stress has a negative and significant effect on employee performance through Organization citizenship behavior (OCB) as an intervening variable, (7) Work discipline has a positive and significant effect on employee performance through Organizational citizenship behavior (OCB) as an intervening variable.